Analisis Pelaporan Dana Zakat dengan Kinerja Keuangan pada Lembaga Keuangan Syariah - Mansyur, Muhamad Ondoh; Haerani, Nurah; Hamidullah, Rizky Eka; Sunarsih, Uun (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2025)
This study aims to assess the role of zakat reporting in relation to the financial performance of Islamic financial institutions, specifically BSI and Panin Dubai Syariah. According to BAZNAS, zakat in Indonesia holds significant economic potential, estimated at IDR 327 trillion, although actual collections remain far below this figure. An interesting phenomenon arises as some Islamic financial institutions in Indonesia have not fully complied with zakat reporting obligations, despite existing regulations. The relationship between zakat reporting and financial performance has thus become a relevant topic for research within the context of Indonesia's Islamic economy. This study employs a literature review method and analyzes financial data from the financial statements of two Islamic financial institutions: BSI and Bank Panin Dubai Syariah. Based on theory and existing literature, the study argues that zakat reporting plays a role and has an impact on financial performance. The results show that zakat reporting has a significant influence on financial performance, particularly in the analysis of ROA and ROE for the period 2021–2023 at BSI and Panin Dubai Syariah, although several challenges still need to be addressed.